Strategies in the development of vaccines to prevent infections with group A streptococcus - Good, Michael F (Landes Bioscience, 2013)
There has long been interest and demand for the development of a vaccine to prevent infections caused by the Gram-positive organism group A streptococcus. Despite numerous efforts utilizing advanced approaches such as genomics, proteomics and bio-informatics, there is currently no vaccine. Here we review various strategies employed to achieve this goal. We also discuss the approach that we have pursued, a non-host reactive, conformationally constrained minimal B cell epitope from within the C-repeat region of M-protein, and the potential limitations in moving forward.